The Link between Analysis Dimension of Strategic Orientation and Firm Performance in Small and Medium Enterprises in the Hospitality Industry in Kenya: The Moderating Role of Top Manager’s Ownership Status - Cheluget, Martha; Koech, JS Caroline (IJAAS, 2018)
Performance of Small and Medium Enterprises (SMEs) is important for the economic success of nations, and strategic orientation is documented as one of the critical success factors for business firms. However, empirical studies have yielded varied results on the influence of the various dimensions of strategic orientation under different conditions. Furthermore most studies have focused on large firms and more so in developed countries. The primary objective of this study was to examine the effect of analysis dimension of strategic orientation on the performance of SMEs in a developing economy. The study employed explanatory research design. Data was collected from a sample of 390 hotel and food service SMEs and was analyzed using descriptive and inferential statistics. Pearson Correlation was used to test for linear relationships between the variables while the research hypotheses were tested using multiple regression models. The findings indicated that Analysis dimension has statistically significant (Î²=0.929, Ï<0.05) and positive effect on firm performance. However, the study found that although top manager’s ownership status had statistically significant direct effect (Î²=0.264, Ï<0.05) on performance, its moderating effect (Î²=0.080, Ï>0.05) on the relationship between analysis dimension and firm performance was not significant. The study thus concluded that Analysis dimension significantly and positively affects firm performance in SMEs regardless of the ownership status of the top managers and recommends for managers and policy makers to focus on analysis strategies in order to enhance firm performance in SMEs.